Women and home survival in Nigeria and Malaysia: A comparative Analysis and lessons for contemporary Nigerian muslim women (2011)
Domestic welfare responsibilities in male-headed households are in some cases shifted to women. The need to make crucial economic decisions due to adverse adjustments in the formal sector of the economy is a plausible factor. This has been found to decrease women's economic earnings. The bid to cope with household management and survival has forced women into the informal sector of the economy. This has reshaped women's work and it has also accentuated gender inequalities. The aim of this paper was to review empirical cases on the subject matter in Nigeria and Malaysia employing secondary data to see the situations of women and different strategies employed in these countries by women as regards home survival. This was done in order to see what Nigerian Muslim women, in particular, may learn from their Malaysian counterpart about household management and survival especially considering the fast modern development of Muslim women in Malaysia. The study found out that Muslim women in Malaysia are better off in home survival strategies than their Nigerian counterparts due to technological development, government assisted programs and loans for single mothers and women entrepreneurs. Therefore, Nigerian governments at the federal and state as well as the municipal arms should assist women, including Muslim women's single mothers, unemployed and entrepreneurs. Muslim women, especially, entrepreneurs should also embrace their technological knowledge like their Malaysian counterparts to enhance their economic development and sustainability.